Secessionism and Austrian Graphic Art 1900-1920 : From the Collection of the Neue Galerie der Stadt Linz. - Neue Galerie der Stadt Linz, Linz (Washington : Smithsonian Traveling Exhibition Service, 1990)
Brosch, Klemens ; Egger-Liezn, Albin ; Franta, Hans ; Gunia, Stascho ; Gütersloh, Albert Paris ; Hauser, Carry ; Herzmanovsky-Orlando ; Fritz V. ; Hofer, Franz ; HOfmann, Egon ; Jungnickel, Ludwig ; Klimt, Gustav ; Kokoschka, Oskar ; Koller-Pinell, Broncia ; etc.
Secessionism and Austrian Graphic Art 1900-1920 : From the Collection of the Neue Galerie der Stadt Linz, Smithsonian Traveling Exhibition Service, Washington, 1990
boek